THE EFFECT OF WORK COMMITMENT AND INTERPERSONAL COMMUNICATION ON CREW WORK SATISFACTION ON THE MT SINDANG SHIP - Deni Farhan (International Journal Management and Economic, 2024)
This study explores how Commitment and Communication influence Job Satisfaction among employees of the MT Sindang. Data analyzed using SPSS 19.00 reveal that both Commitment and Communication have a simultaneous impact on Job Satisfaction. Detailed analysis shows that Commitment significantly correlates with Job Satisfaction, as does Communication. However, the findings do not entirely validate the overall hypothesis, suggesting that further research is needed to fully understand the combined effect of Commitment and Communication on Job Satisfaction. These insights are crucial for organizational management and human resource strategies aiming to enhance employee Job Satisfaction.